Corporate Sustainability and Organizational Change. Case of OMV Petrom - Catalina Soriana Sitnikov; Claudiu George Bocean (Amfiteatru Economic Journal, 2012)
Many corporations have recognized the importance of being perceived as socially responsible to the environment, employees or local community. They have worked hard to be labeled as sustainable organizations. Corporate behavior, however, implies a gap between theory and practice. Therefore, we consider it necessary to study how to transform corporations into sustainable organizations based on organizational change models. The paper brings an original contribution to the study of organizational sustainability by introducing a framework for sustainable organizational change using organizational culture components and Deming's Plan-Do-Check-Act (PDCA) cycle of continuous quality improvement.
Keywords: Q01; L16; 330; sustainability; organizational change; culture management; PDCA; OMV Petrom